2008
DOI: 10.1021/jf802754s
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of [2-14C]Quercetin-4′-glucoside in Rats

Abstract: [2-(14)C]quercetin-4'-glucoside (4 mg/kg body weight) was fed by gavage to rats housed in metabolic cages, and over an ensuing 72 h period, radiolabeled products in body tissues, plasma, feces, and urine were monitored by high-performance liquid chromatography with online radioactivity and MS2 detection. One and 6 h after ingestion, while in the small intestine, the flavonol glucoside was converted to glucuronide and methylated and sulfated derivatives of quercetin, but only trace amounts of these metabolites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(105 citation statements)
references
References 37 publications
(63 reference statements)
5
99
1
Order By: Relevance
“…We and others have reported that glucuronidation in the small intestine plays a key role in quercetin metabolism in rats (Graf et al, 2006;Mullen et al, 2008). Our results further confirm the importance of this organ for first-pass metabolism of flavonoids through glucuronidation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We and others have reported that glucuronidation in the small intestine plays a key role in quercetin metabolism in rats (Graf et al, 2006;Mullen et al, 2008). Our results further confirm the importance of this organ for first-pass metabolism of flavonoids through glucuronidation.…”
Section: Discussionsupporting
confidence: 88%
“…Prolonged quercetin feeding to F344 rats resulted in mainly mono-, di-, or mixed glucuronides or quercetin in intestinal tissue (Graf et al, 2006). In Sprague-Dawley rats, the primary metabolites of quercetin 4Ј-glucoside in intestinal tissue were also glucuronides (Mullen et al, 2008). We also found that SI microsomal quercetin CL int was similar to that of the liver of F344 rats of our previous study (Bolling et al, 2010).…”
Section: Discussionsupporting
confidence: 75%
“…The low urinary recovery (1.5%) of the ingested quercetin leaves a large amount of the ingested dose unaccounted for compared with hesperetin and naringenin. The most likely fate of the absorbed quercetin is excretion via bile (Matsukawa et al, 2009) and further degradation to low-molecular-weight phenolic acids that were not analysed in the current and most previous flavonol bioavailability studies (Mullen et al, 2006(Mullen et al, , 2008. Only small amounts of the 3 0 -methylated form of quercetin, isorhamnetin, were present in the 'juice mix' (1.8 mg/500 ml 'juice mix'), and of this only 4.1 ± 3.3% of isorhamnetin was excreted in urine after 48 h, excluding extensive methylation of quercetin.…”
Section: Resultsmentioning
confidence: 99%
“…[18,19] of myricetin. And its reported fragmentation patterns [20] have been detected in the M2 mass spectra. Therefore, M2 was tentatively identified as 3,4,5-trihydroxyphenylacetic acid that could only be found in feces.…”
Section: Identification Of the Compounds Detected In Rat Biological Smentioning
confidence: 91%